2009
DOI: 10.1111/j.1751-9020.2009.00206.x
|View full text |Cite
|
Sign up to set email alerts
|

From Antiracism to Antiracisms

Abstract: Although antiracism has existed as long as there has been racism, social scientists’ attention to antiracism has increased in the past decade. In this essay, I argue that the body of scholarship on antiracism is characterized by three main strands: (1) a macro focus on the ideology and structure of antiracist social movement organizations, often attempting to distil ‘the real’ antiracism from others deemed not critical or radical enough to qualify; (2) a micro focus on what motivates individuals to become anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 17 publications
(22 reference statements)
0
30
0
1
Order By: Relevance
“…As they engage in counter framing (Feagin, ), the possible outcomes of their antiracism range from integration to autonomy. Research on Black antiracism challenges assumptions about that people of color are inherently antiracist (O'Brien, ). Instead, I find that although all Black antiracists must negotiate emphasized blackness, their approach can range from integrationist to oppositional.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As they engage in counter framing (Feagin, ), the possible outcomes of their antiracism range from integration to autonomy. Research on Black antiracism challenges assumptions about that people of color are inherently antiracist (O'Brien, ). Instead, I find that although all Black antiracists must negotiate emphasized blackness, their approach can range from integrationist to oppositional.…”
Section: Resultsmentioning
confidence: 99%
“…Much of the sociological literature on antiracism focuses on Whites in the United States and Europe (Bowser, ; Brown, ; Cooper, Schaefer, and Brod, 2003; Hartigan, ; Hughey, 2007; Hughey, ; Katz, ; Katz, 2003; Kivel, ; Marty, ; O'Brien, ; O'Brien, ; Segrest, ; Warren, 2010). Whites ultimately perform antiracism in a manner that reinforces rather than weakens White supremacy due to hegemonic whiteness .…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that motivated antiracists, i.e., those who have an internal motivation to respond without prejudice (Plant & Devine, 1998), have a tendency to experience discomfort, distress, guilt, fear, anxiety, anger, inaction and withdrawal (Nile & Straton, 2003;O'Brien, 2009;Tatum, 1992). These emotions can be caused, in part, by a disconnection between an antiracist worldview and 'unconscious' racist feelings, thoughts and behaviours that reflect prevailing social norms (Sommers & Norton, 2006).…”
Section: Introductionmentioning
confidence: 99%